1981
DOI: 10.1111/j.1365-2621.1981.tb01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐amylase and bread properties

Abstract: Commercial baking trials, designed to investigate the effects of a-amylase activity during baking are described. Increasing a-amylase activity changes both the physical and chemical properties of bread, the physical changes resulting in a loss of crumb mechanical strength, and the chemical changes resulting in an increase in the amount of starch degradation products in the bread, and thus an increase in crumb stickiness. Both types of change can cause problems at the bread slicing stage. A reduction in water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The lack of available water usually limits grain yield but gives high protein grain. Low falling numbers are associated with excessive alpha amylase which is associated with negative effects on bread crumb texture and crust color (Chamberlain, Collins, & McDermott, 1981). High grain protein is useful for bread making because the proteins allow the dough to stretch and capture the CO 2 produced from yeast during the dough proofing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of available water usually limits grain yield but gives high protein grain. Low falling numbers are associated with excessive alpha amylase which is associated with negative effects on bread crumb texture and crust color (Chamberlain, Collins, & McDermott, 1981). High grain protein is useful for bread making because the proteins allow the dough to stretch and capture the CO 2 produced from yeast during the dough proofing.…”
Section: Introductionmentioning
confidence: 99%
“…It is a measurement of alpha-amylase activity. Low falling numbers are associated with excessive alpha amylase which is associated with negative effects on bread crumb texture and crust color (Chamberlain, Collins, & McDermott, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The MF addition to flour increases gas production in the dough, improves crust colour formation and flavour profile of product and provides a better crumb moisture retention. Malt a-amylases are necessary for optimal yeast growth and gas production (Chamberlain et al, 1981;Hrusˇkova´et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that addition of α-amylase improves dough-handling properties, increases loaf volume and shelf life of bread [145][146][147] . It is generally believed that α-amylases may affect dough properties in three ways, namely, by the formation of sugars that can be fermented by yeast, by the break down of the damaged-starch fraction, and by the formation of dextrins.…”
Section: α-Amylasesmentioning
confidence: 99%